Interaction of Cholesterol With the Human SLC1A5 (ASCT2): Insights Into Structure/Function Relationships - Scalise, Mariafrancesca; Pochini, Lorena; Cosco, Jessica; Aloe, Emma; Mazza, Tiziano; Console, Lara; Esposito, Antonella; Indiveri, Cesare (Frontiers in Molecular Biosciences, 2019)
The human SLC1A5 commonly known as ASCT2 is a sodium-dependent neutral amino acid antiporter involved in transmembrane traffic of glutamine that is exchanged through the cell membrane with smaller amino acids such as serine or threonine. Due to the strong overexpression in human cancers, ASCT2 is widely studied for its relevance to human health. Of special interest are the aspects related to the regulation of its function. The role of cholesterol as a modulator of the transport activity has been studied using a combined strategy of computational and experimental approaches. The effect of cholesterol on the Na+ex-[3H]glutamineex/glutaminein antiport in proteoliposomes has been evaluated by adding Cholesteryl hemisuccinate. A strong stimulation of transport activity was observed in the presence of 75 µg Cholesteryl hemisuccinate per mg total lipids. The presence of cholesterol did not influence the proteoliposome volume, in a wide range of tested concentration, excluding that the stimulation could be due to effects on the vesicles. Cholesteryl hemisuccinate, indeed, improved the incorporation of the protein into the phospholipid bilayer to some extent and increased about three times the Vmax of transport without affecting the Km for glutamine. Docking of cholesterol into the hASCT2 trimer was performed. Six poses were obtained some of which overlapped the hypothetical cholesterol molecules observed in the available 3D structures. Additional poses were docked close to CARC/CRAC motifs (Cholesterol Recognition/interaction Amino acid Consensus sequence). To test the direct binding of cholesterol to the protein, a strategy based on the specific targeting of tryptophan and cysteine residues located in the neighborhood of cholesterol poses was employed. On the one hand, cholesterol binding was impaired by modification of tryptophan residues by the Koshland's reagent. On the other hand, the presence of cholesterol impaired the interaction of thiol reagents with the protein. Altogether, these results confirmed that cholesterol molecules interacted with the protein in correspondence of the poses predicted by the docking analysis